On True and Supposed Humanity in Foreign Historical Cinema of the 21st Century / Об истинной и мнимой человечности в зарубежном историческом кино XXI века - KONSON GRIGORIY R. / КОНСОН Г.Р.; KONSON IRINA A. / КОНСОН И.А. (Наука телевидения)
The article studies the phenomenon of true and supposed humanity in foreign historical films of the beginning of the 21st century. The reason for addressing the topic was the appearance of films devoted to the images of an odious personality and viewed in a new (as opposed to old films about tyrants, such as Caligula by T. Brass; Great Britain, USA, Italy, 1979) humane perspective. Such are the films about Nero (Nero, directed by P. Markus; Italy, Germany, Great Britain, France, Tunisia, 2004), Hitler (Downfall, Germany, France, Italy; directed by O. Hirschbiegel, 2004), which have already outlined a perspective in development, crowned by a film about the family of a death camp commandant (The Boy in the Striped Pyjamas, directed by M. Herman; Great Britain, USA, 2008). The focus here is on the reinterpretation of the main images in the context of revealing some hidden personal features of the protagonists. For this purpose, the evil they have caused is left behind the scenes, and the viewer’s attention is focused on simple “human” emotions: Nero tearfully regrets his crimes, Hitler suffers before committing a suicide, the concentration camp commandant and his wife are horrified by the disappearance of their eight-year-old son in the death camp. By disguising the true nature of the personalities, film creators shift attention from their criminal activities to their “virtuous” everyday life not concerning the war and the military affairs. As a result, the works of art in question reinterpret the established characteristics of recognizable large-scale villains and transform them into ordinary people requiring sympathy. But, contrary to such a free interpretation of humanity, the authors of the article present a different perspective on it, where the studied phenomenon acts as a versatile-heroic one. Therefore, the aim of the article is to specify the phenomenon on the basis of two opposing matrices: 1) the development of humanistic traditions—“exceeding humanity in man” (G.-H. Gadamer), 2) distorting historical facts for the sake of artificial transformation of the representative of evil into a humane one.